Concomitants of paranoia in the general population. - Freeman, D; McManus, S; Brugha, T; Meltzer, H; Jenkins, R; Bebbington, P (2011)
BACKGROUND: Paranoia is an unregarded but pervasive attribute of human populations. In this study we carried out the most comprehensive investigation so far of the demographic, economic, social and clinical correlates of self-reported paranoia in the general population. METHOD: Data weighted to be nationally representative were analysed from the Adult Psychiatric Morbidity Survey in England (APMS 2007; n=7281). RESULTS: The prevalence of paranoid thinking in the previous year ranged from 18.6% reporting that people were against them, to 1.8% reporting potential plots to cause them serious harm. At all levels, paranoia was associated with youth, lower intellectual functioning, being single, poverty, poor physical health, poor social functioning, less perceived social support, stress at work, less social cohesion, less calmness, less happiness, suicidal ideation, a great range of other psychiatric symptoms (including anxiety, worry, phobias, post-traumatic stress and insomnia), cannabis use, problem drinking and increased use of treatment and services. CONCLUSIONS: Overall, the results indicate that paranoia has the widest of implications for health, emotional well-being, social functioning and social inclusion. Some of these concomitants may contribute to the emergence of paranoid thinking, while others may result from it.